Taste Metaphors for Food Description as a Creative Effort by Indonesian Food Vloggers - Adam Muhammad Nur; R. Dian Dia-an Muniroh; Rusdiansyah (Institut Agama Islam Negeri Palopo, 2025)
This study aims to investigate the use of metaphors in the conventional language employed by Indonesian food vloggers when describing food, claiming it as a form of linguistic creativity influenced by their cognitive capabilities. Creativity in language is a gift that humans inherently possess, enabling them to freely communicate, share information, and convey intentions. This premise is grounded in the claim that humans cognitively possess mental faculties allowing for unrestricted language production (Saeed, 2003). Traditionally, metaphors are understood as a literary style often used in poetry, novels, or drama. However, in reality, humans are inseparable from metaphors (Lakoff in Lakoff and Johnson, 2003). Cognitively, humans use metaphors to facilitate understanding by associating one term with another in language (Lakoff in Jackendoff and Aaron, 1991). The data source for this research comprises several videos from Indonesian food vloggers, including 4 videos each from Anak Kuliner, Boengkoes Network, Mamank Kuliner, and Nex Carlos. These vloggers are well-known in Indonesia with a substantial number of subscribers. The research employs a qualitative descriptive method, which allows for a comprehensive explanation of phenomena observed in the data. The analysis reveals that in describing food, food vloggers tend to use structural metaphors more frequently than other types of metaphors, with 26 occurrences recorded. This finding indicates that equating the domain of food taste with another domain structurally makes it easier to convey and understand abstract taste experiences through the shared experiences of vloggers and their audiences